Potensi sentra olahan ubi kayu dan mitigasi bencana di Desa Kranggan, Galur, Kulon Progo - Paramita, Brigitta Laksmi; Pratama, Sergio; Novianti, Fatimah; Gurusinga, Christophel; Satriani, Amanda Putri Eriandina; Marhaeni, Maria Btari Larasati; Lo, Christina Natalia Kharis; Katelya, Dea; Yuniarka, Gisela Radiastasha; Putrianti, Pita Desi; Malau, Deon Natanael (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Kuliah Kerja Nyata (KKN) are part of a mandatory activity to fulfill student obligations, namely community service, KKN in batch 80 is carried out online due to the covid-19 pandemic. Therefore, this research was conducted to fulfill the task given by Atma Jaya University Yogyakarta. The Kranggan Village area is one of the villages located in the Galur sub-district, Kulon Progo Regency which is located close to the southern coast of the island of Java. Therefore, it is necessary to have comprehensive efforts in policy making to reduce the risk caused by natural disasters such as doing mitigation. In addition, this study aims to educate the Kranggan village community in increasing search results from cassava plants, where the Kranggan village area has 91.0 hectares of land for cassava plants in 2018. Data collection techniques in this research are observation, collection of literature studies from the internet and discussions with lecturers. The results of this study were made together with a pocket book or e-book entitled